Should We Look beyond Revised International Prognostic Scoring System: A Retrospective Observational Study of Progression of Myelodysplastic Syndrome to Acute Leukemia - Nagarjun, Bangalore Rammohan; Kalaharaghini, Rajashekar; Sawhney, Jyoti; Trivedi, Pina J.; Dhandapani, Karthik; Parikh, Biren (Indian Journal of Medical and Paediatric Oncology, 2021)
Introduction Myelodysplastic syndrome (MDS) is a clonal stem cell disorder and heterogeneous condition resulting in peripheral cytopenias with marrow dysplasia due to ineffective hematopoiesis. The revised International Prognostic Scoring System (IPSS-R) predicts the risk of progression to acute leukemia (AL). Indian data on MDS and its progression to AL are limited. Additionally, the cytogenetic findings are dictated by patients' racial background. Study intended to analyze the cytogenetic profile of the patients with MDS.Objectives This study aimed to (1) evaluate the clinicohematologic and morphologic spectrum of newly diagnosed MDS cases, (2) evaluate the cytogenetic profile of these cases, and (3) study the cases progressed to AL.Materials and Methods MDS cases diagnosed and followed-up during a 5-year study period, from January 2015 to December 2019, were included in the study and the study was conducted at regional cancer center in Western India. De novo diagnosed MDS cases with complete workup were considered and MDS due to secondary causes were excluded. Baseline clinical, hematologic findings were tabulated along with cytogenetics and risk stratified as per IPSS-R, and their progression was studied.Results A total of 63 cases of de novo MDS were diagnosed over a period of 5 years with 45 cases on follow-up and 15 cases (33.3%) progressed to AL. Maximum number of cases belonged to MDS-excess blast (EB) category accounting to 48 cases (76.1%). Apparently normal karyotyping was the commonest cytogenetic finding in 33 MDS cases (61.2%) and in 8 cases that progressed to AL (53.4%).Conclusion MDS cases diagnosed at relatively early age were at higher risk of progression to AL. Majority of the cases that progressed to AL were risk stratified in high and very high risk groups and 10 cases which progressed to AL belonged to good category, interestingly apparent normal karyotyping was the commonest cytogenetic finding in more than 50% of the cases progressed to AL. Molecular mutations could only explain this progression and studies integrating molecular mutations with present IPSS-R scoring system should be conducted, as it could translate into better risk stratification and help in early identification and better management of cases at risk in progression to AL.
Keywords: myelodysplastic syndrome; acute leukemia; International prognostic scoring system; cytogenetics